SopB-Mediated Recruitment of SNX18 Facilitates Salmonella Typhimurium Internalization by the Host Cell - Liebl, David; Qi, Xiaying; Zhe, Yang; Barnett, Timothy C.; Teasdale, Rohan D. (Frontiers in Cellular and Infection Microbiology, 2017)
To invade epithelial cells, Salmonella enterica serovar Typhimurium (S. Typhimurium) induces macropinocytosis through the action of virulence proteins delivered across the host cell membrane via a type III secretion system. We show that after docking at the plasma membrane S. Typhimurium triggers rapid recruitment of cytosolic SNX18, a SH3-PX-BAR domain sorting nexin protein, to the bacteria-induced membrane ruffles and to the nascent Salmonella-containing vacuole. SNX18 recruitment required the inositol-phosphatase activity of the Salmonella effector SopB and an intact phosphoinositide-binding site within the PX domain of SNX18, but occurred independently of Rho-GTPases Rac1 and Cdc42 activation. SNX18 promotes formation of the SCV from the plasma membrane by acting as a scaffold to recruit Dynamin-2 and N-WASP in a process dependent on the SH3 domain of SNX18. Quantification of bacteria uptake revealed that overexpression of SNX18 increased bacteria internalization, whereas a decrease was detected in cells overexpressing the phosphoinositide-binding mutant R303Q, the ΔSH3 mutant, and in cells where endogenous levels of SNX18 were knocked-down. This study identifies SNX18 as a novel target of SopB and suggests a mechanism where S. Typhimurium engages host factors via local manipulation of phosphoinositide composition at the site of invasion to orchestrate the internalization process.